2015
DOI: 10.5966/sctm.2014-0298
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Disease Persistence in Gastrointestinal Stromal Tumors

Abstract: Gastrointestinal stromal tumors (GISTs) are one of the most common connective tissue cancers. Most GISTs that cannot be cured by surgery respond to molecularly targeted therapy (e.g., with imatinib); however, tumor cells persist in almost all patients and eventually acquire drug-resistant mutations. Several mechanisms contribute to the survival of GIST cells in the presence of imatinib, including the activation of "escape" mechanisms and the selection of stem-like cells that are not dependent on the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…1 GISTs arise from the interstitial cell of Cajal lineage within the enteric nervous system. 2 Approximately 70% to 80% of all sporadic GISTs have activating genomic alterations in KIT , whereas 5% to 10% have activating genomic alterations in PDGFRA . 3,4 Of the remaining GISTs, 10% to 15% have activation of the Ras pathway ( K/H/N-RAS , BRAF , NF1 ); 2% arise from mutations or deficiencies in the succinate dehydrogenase (SDH) subunits (A, B, C, or D); and a subset occurs as a result of kinase fusions ( ETV6-NTRK3 , FGFR1-TACC1 , or FGFR1-HOOK3 ) or additional mutations in genes, including ARID1A and ARID1B .…”
Section: Introductionmentioning
confidence: 99%
“…1 GISTs arise from the interstitial cell of Cajal lineage within the enteric nervous system. 2 Approximately 70% to 80% of all sporadic GISTs have activating genomic alterations in KIT , whereas 5% to 10% have activating genomic alterations in PDGFRA . 3,4 Of the remaining GISTs, 10% to 15% have activation of the Ras pathway ( K/H/N-RAS , BRAF , NF1 ); 2% arise from mutations or deficiencies in the succinate dehydrogenase (SDH) subunits (A, B, C, or D); and a subset occurs as a result of kinase fusions ( ETV6-NTRK3 , FGFR1-TACC1 , or FGFR1-HOOK3 ) or additional mutations in genes, including ARID1A and ARID1B .…”
Section: Introductionmentioning
confidence: 99%
“…In rare cases, GIST lack a mutant KIT or PDGFRA allele. These tumors may arise from mutations in KIT/PDGFRA signaling intermediates (e.g., NF1, BRAF, KRAS, HRAS ) or deficiency in the mitochondrial succinate dehydrogenase (SDH) complex caused by inactivating SDH subunit (A-D) mutations or epigenetic repression [ 2 , 3 , 8 , 9 ]. Despite their molecular heterogeneity, most GIST share common characteristics, including expression and activation of KIT and PDGFRA.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] SHH, PTCH1, SMO, and GLI1 expression were detected by immunohistochemistry in one study [ 18 ], and chromosome 7p amplification was found to be associated with increased GLI3 expression [ 19 ]. Interestingly, GLI3 has been reported to repress KIT mRNA levels in ICC-like cells of the murine ureter [ 20 ], raising the possibility that GLI3 may contribute to the formation of a KIT low/− GIST cell pool [ 4 ] responsible, in part, for disease persistence during imatinib therapy [ 3 ]. Additionally, conditional PTCH1 inactivation in lysozyme M-expressing murine cells has been reported to lead to the development of PDGFRA + GIST-like lesions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 However, resistance to imatinib mesylate is increasing and complete remission is rare, highlighting the necessity to improve our molecular understanding of GIST pathophysiology. 5 Cell dedifferentiation is a central mechanism in the initiation of neoplastic transformation and therapeutic resistance. [9][10][11] It involves loss of lineage-specific gene expression and regression from a specialized tissue to a more primitive state of development through expression of genes that govern embryonic cell-fate specification.…”
mentioning
confidence: 99%